The Importance of Connection to Others in QoL in MSA and PSP - Louise Wiblin; Rory Durcan; Mark Lee; Katie Brittain (Parkinson's Disease)
Multiple System Atrophy (MSA) and Progressive Supranuclear Palsy (PSP) are atypical Parkinsonian disorders with extended morbidity and reduced lifespan, known to have marked and early impact upon quality of life (QoL). This study aimed to address the lack of studies in the literature regarding personal perspectives on QoL in MSA and PSP in both patients and carers. Participants took part in qualitative, in-depth interviews in the North East of England, exploring what impacts their QoL and their experiences of living with these complex conditions. Connection to others was found to be a prevailing theme, encompassing difficulty communicating, social isolation, impact on personal relationships, and stigma. This work is helpful in that it emphasises the personal experiences of these patients and carers, which can provide insights into important areas for clinical service planning and best clinical management of individual patients as well as considerations for future research into QoL in these rare disorders.